Management of Skin Toxicity Related to the Use of Imatinib Mesylate (STI571, Glivec™) for Advanced Stage Gastrointestinal Stromal Tumours. (2005) - Scott, Lucy C.; White, Jeff D.; Reid, Robin; Cowie, Fiona
Abstract : Skin toxicity is a common side-effect of treatment with imatinib mesylate (STI571, Glivec ™ ) in advanced gastrointestinal stromal tumours (GIST) and chronic myeloid leukaemia. The optimal duration of treatment with imatinib mesylate in GIST has not yet been established, as durable remissions have been observed in patients. It is, therefore, important to develop strategies to deal with common side-effects of what may be a long-term treatment. Here we report the case of a patient with advanced GIST who developed a cutaneous drug reaction secondary to imatinib mesylate and the various management options that may be employed depending upon the severity of the toxicity. The case and literature are discussed.